2019
DOI: 10.1021/acs.jctc.9b00428
|View full text |Cite
|
Sign up to set email alerts
|

Standard Binding Free Energy of a SIM–SUMO Complex

Abstract: Interaction of the small ubiquitin-related modifier (SUMO) and peptides containing a SUMO-interacting motif (SIM) has attracted a lot of interest in recent years, yet their structural properties and relationships between the composition of the peptide and binding free energy are not completely understood. We perform molecular dynamics simulations of the complex formed by SUMO and a peptide containing the tight-binding SIM of the protein inhibitor of activated STAT. The calculated standard binding free energy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Large-scale studies on pharmaceutically relevant ligandreceptor pairs indicate that free energy estimates from MD simulation exhibit systematic errors in the range of 1 kcal/ mol (36). The statistical error found for affinity estimates with the method used in this study is typically much lower, even when shorter simulation times were used (18,37). This suggests that statistical errors can indicate higher accuracy than we actually have.…”
Section: Estimation Of Affinitiesmentioning
confidence: 58%
See 1 more Smart Citation
“…Large-scale studies on pharmaceutically relevant ligandreceptor pairs indicate that free energy estimates from MD simulation exhibit systematic errors in the range of 1 kcal/ mol (36). The statistical error found for affinity estimates with the method used in this study is typically much lower, even when shorter simulation times were used (18,37). This suggests that statistical errors can indicate higher accuracy than we actually have.…”
Section: Estimation Of Affinitiesmentioning
confidence: 58%
“…We used atomistic molecular dynamics (MD) simulations to investigate structural properties of complexes formed by peptides containing SIM2 or SIM3 of RNF4 and SUMO3 (see Table 1). We used the method of Woo and Roux (17) to estimate the affinities of the SIM2 and SIM3 peptides to SUMO, which also directly allowed us to quantify the contribution of either binding orientation to the overall affinity (18).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested [ 13 ] that the parallel binding by the PIASX SIM is preferred because the parallel orientation optimizes non-polar contacts between the hhxh SIM core and SUMO. This conclusion is challenged, however, by a molecular dynamics simulation of binding between the SIM in PIAS1 (a close relative of PIASX) and SUMO-3 [ 21 ]. This simulation suggests that the core binds with similar affinity to the SUMO hydrophobic groove in either the parallel or the antiparallel orientation.…”
Section: Sim Structure and Regulation Of Sim/sumo Complex Formationmentioning
confidence: 99%
“…It has been shown that the geometrical approach accurately predicts protein−ligand binding energies. 44,45 We used the default set up of the binding free energy estimator as described by Chipot and coworkers. 46 More details on theoretical background of the geometrical (i.e., potential-of-mean-force) free energy calculations can be obtained elsewhere.…”
Section: Binding Energy Calculationsmentioning
confidence: 99%